Female gender and mortality in ST-segment-elevation myocardial infarction treated with primary PCI. Issue 4 (25th April 2022) - Paradossi, Umberto; Taglieri, Nevio; Massarelli, Giulia; Palmieri, Cataldo; De Caterina, Alberto Ranieri; Bruno, Antonio Giulio; Taddei, Alessandro; Nardi, Elena; Ghetti, Gabriele; Palmerini, Tullio; Trianni, Giuseppe; Mazzone, Annamaria; et al.
Abstract : Aims: To investigate gender difference in mortality among patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous angioplasty (PPCI). Methods: We analyzed data from the prospective registries of two hub PPCI centres over a 10-year period to assess the role of female gender as an independent predictor of both all-cause and cardiac death at 30 days and 1 year. To account for all confounding variables, a propensity score (PS)-adjusted multivariable Cox regression model and a PS-matched comparison between the male and female were used. Results: Among 4370 consecutive STEMI patients treated with PPCI at participating centres, 1188 (27.2%) were women. The survival rate at 30 days and 1 year were significantly lower in women (Log-rank P -value < 0.001). At PS-adjusted multivariable Cox regression analysis, female gender was independently associated with an increased risk of 30-day all-cause death [hazard ratio (HR) = 2.09; 95% confidence interval (CI): 1.45–3.01, P < 0.001], 30-day cardiac death (HR = 2.03;95% CI:1.41–2.93, P < 0.001), 1-year all-cause death (HR = 1.45; 95% CI:1.16–1.82, P < 0.001) and 1-year cardiac death (HR = 1.51; 95% CI:1.15–1.97, P < 0.001). For the study outcome, we found a significant interaction of gender with the multivessel disease in females who were at increased risk of mortality in comparison with men in absence of multivessel disease. After the PS matching procedure, a subset of 2074 patients were identified. Women still had a lower survival rate and survival free from cardiac death rate both at 30-day and at 1-year follow-up. Conclusion: As compared with men, women with STEMI treated with PPCI have higher risk of both all-cause death and cardiac mortality at 30-day and 1-year follow-up.